IDENTIFIKASI SAKARIN, SIKLAMAT, DAN NATRIUM BENZOAT SERTA KARAKTERISTIK SUSU KEDELAI YANG DIJUAL DI PASAR TRADISIONAL WILAYAH JIMBARAN, BALI SELAMA PENYIMPANAN - Olivea Herman, Novelita; Ari Yusasrini, NL.; Kencana Putra, I Nengah (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 4 (2020): Jurnal ITEPADO - 10.24843/itepa.2020.v09.i04.p11, 2020)
This study aims to identify saccharin, cyclamate, and sodium benzoate in soy milk circulating in traditional markets in the Jimbaran region, determine the percentage of soy milk samples in traditional markets in the Jimbaran region that contain saccharin, cyclamate, and sodium benzoate, and determine the characteristic of milk soybeans in the traditional markets of the Jimbaran region, Bali during storage. This study uses a survey method with saturation sampling technique. Saccharin, cyclamate and sodium benzoate were analyzed qualitatively and quantitatively while the characteristic of soy milk were observed included pH, total plate count, and sensory assessment. Saccharin, cyclamate, sodium benzoate, pH, total plate count, and sensory assessment were analyzed using descriptive methods. The results showed that soy milk in traditional markets in the Jimbaran region did not contain saccharin, 80% used cyclamate, 100% used sodium benzoate, and characteristics of soy milk in traditional markets in Jimbaran, Bali during 8 hours storage has pH between 6.8 to 8.34, as much as 70% of soy milk has total plate count less than 106 CFU/ml, and it is still well consuming because the color has the like criteria, aroma and flavor has the neutral criteria and very not acidic.